Bimtek Penyusunan Proposal Pembiayaan UMKM di Desa Narawita - Suyatna, Nano; Rivaldy, Javier (Ma'soem University, 2024)
This community service activity aims to provide technical guidance to Micro, Small and Medium Enterprises (MSMEs) in Narawita Village in preparing effective financing proposals to be submitted to banking and non-banking institutions. The methods used include training, workshops and individual mentoring. Data was obtained through pre and post training evaluations, as well as interviews with participants. The results show a significant increase in the ability to make financing proposals where previously they felt confused. preparation of a comprehensive and effective financing proposal, participants demonstrate significant understanding after each session, participants can identify and understand the important parts of a financing proposal, participants can effectively apply the techniques learned, such as writing an attractive executive summary, market-based analysis data, as well as more realistic financial planning. Participants feel more confident in preparing proposals that meet the funder's expectations. Participants' level of confidence in preparing proposals increased to 70%, based on the results of the post-training survey.